2009
DOI: 10.1007/s11103-009-9508-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential and dynamic regulation of miR398 in response to ABA and salt stress in Populus tremula and Arabidopsis thaliana

Abstract: MicroRNAs (miRNAs) are endogenous small RNAs of ~22 nucleotides (nt) that play a key role in down regulation of gene expression at the post-transcriptional level in plants and animals. Various studies have identified numerous miRNAs that were either up regulated or down regulated upon stress treatment. Here, we sought to understand the temporal regulation of miRNAs in different plant species under abscisic acid (ABA) and salt (NaCl) stress. Our results showed that the regulation of miR398 in response to ABA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
134
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(151 citation statements)
references
References 38 publications
14
134
1
2
Order By: Relevance
“…However, our results showed that Os-miR397b.2 was induced by heat stress. This kind of differential regulation of a miRNA between different plant species was also reported in the case of miR398 (Jia et al, 2009). In poplar, miR398 was induced by ABA treatment or salt stress.…”
Section: Environmental Stress-regulated Mirnassupporting
confidence: 64%
See 1 more Smart Citation
“…However, our results showed that Os-miR397b.2 was induced by heat stress. This kind of differential regulation of a miRNA between different plant species was also reported in the case of miR398 (Jia et al, 2009). In poplar, miR398 was induced by ABA treatment or salt stress.…”
Section: Environmental Stress-regulated Mirnassupporting
confidence: 64%
“…In poplar, miR398 was induced by ABA treatment or salt stress. However, the expression of miR398 in Arabidopsis was decreased by salt stress or by ABA treatment (Jagadeeswaran et al, 2009;Jia et al, 2009).…”
Section: Environmental Stress-regulated Mirnasmentioning
confidence: 99%
“…Recent evidence also uncovered the role of small RNA molecules in regulating plant stress responses (Sunkar, 2010;Khraiwesh et al, 2012). Microarray analysis and deep-sequencing data demonstrated that the accumulation of a number of miRNAs is affected by abiotic stresses (Sunkar and Zhu, 2004;Reyes and Chua, 2007;Zhou et al, 2007Zhou et al, , 2008Liu et al, 2008;Jia et al, 2009), implying a potential role of miRNAs in abiotic stress responses. In Arabidopsis, the expression of MIR395, MIR398, and MIR399 is induced by sulfate, copper, and phosphate deprivation, respectively, and their subsequent down-regulation of target genes is essential for nutrient reallocation (Fujii et al, 2005;Jagadeeswaran et al, 2009;Kawashima et al, 2009).…”
mentioning
confidence: 99%
“…For instance miR160 and miR417 were down-regulated in response to abscisic acid in Arabidopsis, whereas miR169 and miR393 were up-regulated (Jia et al, 2009). There is a good example which shows multiple target of one miRNA.…”
Section: Role Of Non-coding Rnas In Abiotic Stress Of Plantmentioning
confidence: 99%